2021
DOI: 10.1016/j.ijscr.2021.105837
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic assisted ERCP in patient with Roux-en-Y gastric bypass. A case report

Abstract: Highlights Choledocholithiasis in Roux-en-Y patients is a therapeutic challenge for both surgeons and endoscopists. Prophylactic cholecystectomy is not recommended in bariatric surgery. Laparoscopic assisted-ERCP is a safe and feasible intervention. B-ERCP and EDGE are two valid alternatives B-ERCP and EDGE are two valid alternatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
6
0
1
Order By: Relevance
“…Even if the underwater technique is primarily used to perform colonoscopy, the underwater-ERCP using a cap-assisted pediatric colonoscope was recently proposed in six patients with altered anatomy as an alternative, achieving a success rate of 100% without any AEs [ 19 ]. Furthermore, many case reports have been published during the last decade, showing alternative techniques for ERCP in different scenarios, varying from management of Mirizzi syndrome in Billroth II reconstruction to cholangiocarcinoma in RYGB [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In 2006, the short length double-balloon enteroscopy (s-DBE) was firstly used to perform ERCP in RYGB patients [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even if the underwater technique is primarily used to perform colonoscopy, the underwater-ERCP using a cap-assisted pediatric colonoscope was recently proposed in six patients with altered anatomy as an alternative, achieving a success rate of 100% without any AEs [ 19 ]. Furthermore, many case reports have been published during the last decade, showing alternative techniques for ERCP in different scenarios, varying from management of Mirizzi syndrome in Billroth II reconstruction to cholangiocarcinoma in RYGB [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In 2006, the short length double-balloon enteroscopy (s-DBE) was firstly used to perform ERCP in RYGB patients [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association between an extreme weight loss from gastric bypass and the increased risk of developing biliary disorders is well established [4][5][6][7] . However, prophylactic cholecystectomy is still controversial 1,3,5 . Some authors reported an increased risk of postoperative complications due to technical surgery issues, such as surrounding visceral fat and sub-optimal placement of the ports and a significantly longer operative time when cholecystectomy is performed simultaneously 3,6,8 .…”
Section: Discussionmentioning
confidence: 99%
“…However, prophylactic cholecystectomy is still controversial 1,3,5 . Some authors reported an increased risk of postoperative complications due to technical surgery issues, such as surrounding visceral fat and sub-optimal placement of the ports and a significantly longer operative time when cholecystectomy is performed simultaneously 3,6,8 . Only patients with biliary symptoms in the past or at time of bariatric surgery should be submitted to cholecystectomy 9,10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations